An Improved Protocol for the Morita‐Baylis‐Hillman Reaction Allows Unprecedented Broad Synthetic Scope. Issue 9 (19th January 2022) - Camilo, Nilton S.; Santos, Hugo; Zeoly, Lucas A.; Fernandes, Fábio S.; Rodrigues, Manoel T.; Silva, Thiago S.; Lima, Samia R.; Serafim, José Cláudio; de Oliveira, Aline S. B.; Carpanez, Arthur G.; Amarante, Giovanni W.; Coelho, Fernando
Abstract: The Morita‐Baylis‐Hillman (MBH) reaction has been stablished as an important C−C bond‐forming transformation between carbonyl‐containing compounds and activated olefins. However, the slow reaction rate usually observed with electron‐rich electrophilic partners hinders a more widespread use of this reaction. In order to overcome this drawback, the effects of several Brønsted acids on the rate of DABCO‐catalyzed MBH reactions were evaluated. The protocol is operationally simple, involving neat and open‐flask conditions, and is compatible with a wide range of reagents. We suggest a general acid catalysis mechanism to be responsible for the rate increase. The synthetic versatility of the MBH adducts is exemplified with a two‐steps diastereoselective synthesis of the natural product (±)‐sitophilure. We hope this acid‐mediated protocol to have potential use as a general methodology for the MBH reaction. Abstract : By the combination of DABCO and acetic acid under solvent‐free conditions, the Morita‐Baylis‐Hillman reaction rate of both activated and non‐activated aldehydes increased significantly. The disclosed procedure is operationally simple and is compatible with a wide array of both nucleophilic and electrophilic reaction partners.